PERJANJIAN PEMBORONGAN JASA KONSTRUKSI DI LINGKUNGAN PT. KERETA API INDONESIA (PERSERO) (STUDI PADA KONTRAK PENGADAAN JASA PEMBANGUNAN JALUR KERETA API BATU CEPER – BANDARA SOEKARNO-HATTA) - Arief Wisnu Wardhana (SOL JUSTICIA, 2022)
PT.Kereta Api Indonesia (Persero) is one of the State-Owned Enterprises that carries out business activities in the transportation sector, has a mission as a public company and is profit oriented and has a vision and mission, namely to provide mass transportation products / services that are safe, comfortable, environmentally friendly and on time. . To support the achievement of the company's goals in its Business Process PT.Kereta Api Indonesia (Persero) also plays an active role in building transportation infrastructure in order to contribute maximum added value / benefits to improving services to the Government, society and other stakeholders consistently. This type of legal research used is normative juridical. This study uses library research and is corroborated by field data. The sampling technique was using purposive sampling technique. Field data collection techniques used interviews and data collection tools in the form of interview guidelines. The data analysis technique used a qualitative descriptive analysis technique. The results showed that the method of selecting a construction service provider at PT.Kereta Api Indonesia (Persero) was carried out by selecting one of the most appropriate, effective and efficient methods, namely Open Auction, Direct Selection / Selection, Contest, Direct Appointment, Competition / Beauty Contest. , and Self-Management. Where in this study the method of choosing a construction service provider is carried out by Direct Selection / Selection of State-Owned Enterprises. Whereas if there is a dispute or any difference that arises between the parties in implementing the agreement as far as possible, it will be resolved by deliberation and consensus. The results of the deliberation will be stated in a written statement which is generally binding and must be signed by the parties.